THE EFFECT OF BRAND IMAGE ON DECISIONS PURCHASE OF YAMAHA NMAX MOTORCYCLES IN MAHKOTA MOTOR BANGKINANG KOTA - Renaldi Putra; Supardi Supardi; Litra Diantara (STIE Bangkinang Publishing, 2021)
This study aims to determine the effect of brand image on purchasing decisions for Yamaha NMax motorbikes at Mahkota Motor Bangkinang Kota. Population of this study were customers of Yamaha NMax motorbikes at Yamaha Mahkota Motor Bangkinang Kota Dealer. The sample was carried out by purposive sampling method so that the sample in this study became 60 customers. The data collection techniques used were questionnaires and research files. The data analysis technique used is simple linear regression analysis. Based on the results of the study, it can be concluded that brand image has an effect on purchasing decisions. There is a strong relationship between brand image and purchasing decisions and the contribution of the independent variable to the dependent variable is 69.0%.